(untitled) (GESTIÓN Y TENDENCIAS, 2021)
The year 2020 has brought about a rupture of major proportions in everyday life. Our ways of dwelling, of producing, of relating to one another have been interrupted —halted, rather— and with that we have faced the abrupt and compulsory opportunity to observe ourselves and reflect. What we are living through today is not merely a health emergency or a public health problem. In a globalized world articulated through dynamic and competitive market relations, the halt and the confinement have wrought havoc. What emerges as still more serious is the lack of alternatives for organizing the ways of sustaining the materiality of life, as a direct consequence of a monotone and hegemonic economic conception that was left without a "value proposition" in the face of an "externality" it never modeled. Correspondingly, the management strategies that arose under the shelter of that economic vision, and which have been widely and hegemonically disseminated through traditional business education, also reach their limit. A cursory glance at the contents and methodologies of academic programs in the discipline of management suffices to make us realize that we continue educating for a world that no longer exists. It is urgent, more pressing than ever, to review, revisit, and challenge what we have understood until now as business education.